Blocking of Caspases Exerts Anti-Inflammatory Effects on Periodontal Cells - Panahipour, Layla; Cervantes, Lara Cristina Cunha [UNESP]; Abbasabadi, Azarakhsh Oladzad; Sordi, Mariane Beatriz; Kargarpour, Zahra; Gruber, Reinhard (MDPI, 2022)
Periodontitis is an inflammatory process that is associated with caspase activity. Caspases could thus become molecular targets for the modulation of the inflammatory response to harmful factors, such as lipopolysaccharides (LPS) and TNFα. Here, the impact of the pan-caspase inhibitor Z-VAD-FMK (carbobenzoxy-valyl-alanyl-aspartyl-[O-methyl]-fluoro-methyl ketone) on the modulation of the LPS-induced inflammatory response of murine RAW 264.7 cells and primary macrophages was examined. Moreover, the inflammatory responses of human gingival fibroblasts, HSC2 oral squamous carcinoma cells and murine ST2 mesenchymal fibroblasts when exposed to TNFα were studied. Data showed that Z-VAD-FMK significantly lowered the inflammatory response of RAW 264.7 cells and primary macrophages, as indicated by the expression of IL1 and IL6. In murine ST2 mesenchymal fibroblasts, the TNFα-induced expression of CCL2 and CCL5 was significantly reduced. In human gingival fibroblasts and HSC2 cells, Z-VAD-FMK considerably reduced the TNFα-induced expression of CXCL8 and CXCL10. These findings suggest that pharmacological blocking of caspases in an inflammatory environment lowers the expression of cytokines and chemokines in periodontal cells.
Keywords: caspase; fibroblast; in vitro; inflammation; macrophage; periodontitis